2022
DOI: 10.1101/2022.06.01.494310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal obesity increases hypothalamic miR-505-5p expression in mouse offspring leading to altered fatty acid sensing and increased intake of high-fat food

Abstract: In utero exposure to maternal obesity programs a susceptibility to develop obesity. Animal models have shown that offspring obesity is often preceded by increased food intake, however, the mechanisms that mediate these changes are not understood. Using a mouse model of maternal diet-induced obesity we observed increased intake specifically of a high-fat pellet in adult offspring of obese mothers. Through small RNA sequencing, we identified programmed overexpression of miR-505-5p in the hypothalamus of offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Our group has shown that programmed cell-autonomous upregulation of miR-126 in adipose tissue of offspring of obese mothers is responsible for downregulation of insulin receptor substrate 1 and lunapark, contributing to insulin resistance [ 55 ] and ER stress [ 56 ] in these animals. We have also shown that exposure to maternal obesity causes upregulation of miR-505-5p in the fetal hypothalamus, and downregulation of targets that are related to fatty acid sensing pathways [ 57 ]. Over-expression of miR-505-5p in the adult mouse brain causes increased intake of a high-fat diet, suggesting that programmed over-expression of this miRNA after exposure to maternal obesity could underlie altered food choices in offspring that lead to obesity.…”
Section: Epigenetic Mechanisms In the Inter-generational Programming ...mentioning
confidence: 99%
“…Our group has shown that programmed cell-autonomous upregulation of miR-126 in adipose tissue of offspring of obese mothers is responsible for downregulation of insulin receptor substrate 1 and lunapark, contributing to insulin resistance [ 55 ] and ER stress [ 56 ] in these animals. We have also shown that exposure to maternal obesity causes upregulation of miR-505-5p in the fetal hypothalamus, and downregulation of targets that are related to fatty acid sensing pathways [ 57 ]. Over-expression of miR-505-5p in the adult mouse brain causes increased intake of a high-fat diet, suggesting that programmed over-expression of this miRNA after exposure to maternal obesity could underlie altered food choices in offspring that lead to obesity.…”
Section: Epigenetic Mechanisms In the Inter-generational Programming ...mentioning
confidence: 99%